Franchise Agreement in Civil Law Perspective - Sisca Ferawati Burhanuddin (Enrichment : Journal of Management, 2021)
In the current era of globalization, development in the business sector has a very high level of competition, to make it easier for someone in their efforts to maintain their business and government efforts to innovate through franchise activities. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that specifically franchise activities are an agreement involving two or more individuals in which it forms an agreement involving the law as the legal basis, franchise activities provide significant benefits very big for the perpetrators because this activity emphasizes a cooperation and is mutually binding on each other, this business concept involves the franchisor to the franchiseethen becomes a legal institution that regulates the franchise agreement, as 9 of 1995 concerning Small Business, which reads that the franchise pattern is a partnership relationship in which the franchisee grants license rights, trademarks and distribution channels of his company to franchiseeaccompanied by assistance. management guidance.